Reconstruction of the Occipital and Parietal Congenital Defect with 3D Custom-Made Titanium Prosthesis: A Case Report with Four and a Half Years of Follow-Up and a Brief Review of Literature - Farnoush Mohammadi; Abbas Azari; Nariman Nikparto; Heliya Ziaei (Case Reports in Dentistry)
Management of patients with congenital skull defects requires a multidisciplinary approach. Considering the defect’s location and size, brain protection, and the cosmetic outcome makes such reconstructions challenging. Due to limited resemblance to skull contour and donor site morbidity of autogenous bone grafts, alloplastic materials are widely used for skull reconstructions. Titanium alloys have proper strength values, low infection rates, favorable osseointegration property, and excellent marginal adaptability when manufactured by computer-aided design (CAD) and computer-aided manufacturing (CAM). A 13-year-old female patient presented with congenital defects at the superior third of occipital bone and posterior thirds of the bilateral parietal bones. On CT scan, the exact size and shape of the defect were determined. Using CAD/CAM, a 3D virtual model of the prosthesis was designed and then printed with titanium alloy (TiAl6V4) via additive manufacturing method. The prosthesis was placed on the defect in a total surgery time of only 90 minutes. On 4.5 years of follow-up, the contour of the skull was ideal and the skin over the defect and neurologic status was intact. Due to their biocompatibility and rigidity, custom-made titanium prostheses are promising options for reconstructing complex skull defects.